Lipidomics changes in bronchoalveolar lavage fluid of refractory mycoplasma pneumoniae pneumonia: LC-MS-based analysis of potential biomarkers and pathogenesis - Ma, Miao; Shi, Jiao; Wang, Weigang; Huang, Haijuan; Li, Xiaofei (Frontiers in Pediatrics, 2025)
BackgroundPrevious studies have reported the application of metabolomics in infectious diseases, but little is known about the potential function of bronchoalveolar lavage fluid (BALF) metabolites in children with (mycoplasma pneumoniae pneumonia) MPP and (refractory mycoplasma pneumoniae pneumonia) RMPP.MethodsIn this study, untargeted lipidomic analysis of BALF in MPP patients (n = 14) and RMPP patients (n = 14) was performed based on the liquid chromatograph-mass spectrometry (LC-MS) method. Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) was applied to analyze the resultant dataset. Differential metabolites with variable importance in the projection (VIP) >1.5, P < 0.05, and |log2FC| > 1 were subjected to multivariate receiver operating characteristic (ROC) analysis to determine the discriminatory power and reliability of potential biomarkers. The potential significance of the differential metabolites was further demonstrated by correlation analysis between the identified differential markers and clinical inflammatory and cardiovascular indicators.ResultsThirteen differential lipids were found between RMPP and MPP, among which there were three significantly up-regulated differential metabolites (DG(34:4e), PC(36:5), SM(d38:3)), and the areas under the curves (AUCs) of all of them were greater than 0.8, and among the up-regulated differential metabolites of lipids between RMPP and MPP, DG(34:4e) and SM(d38:3) were positively correlated with Hydroxybutyrate Dehydrogenase (HBDH), Lactate Dehydrogenase (LDH), Creatine Kinase (CK), D-Dimer, and Fibrin Degradation Products (FDP).ConclusionThis is the first study to analyze the lipidomic features of BALF to differentiate between RMPP and MPP. The lipidomics of BALF in patients with RMPP was significantly altered and closely correlated with clinically relevant indicators. These data may contribute to the understanding of the pathogenesis of RMPP and the discovery of new biomarkers and therapeutic targets for RMPP.